The Role of Platelet-Rich Plasma in the Management of Ankle Osteoarthritis: A Systematic Review. - Ortega-Castillo, Miguel; Gómez-Cáceres, Abel; Medina-Porqueres, Iván (MDPI, 2024)
Ankle osteoarthritis (OA) is characterized by intraarticular, activity-related pain. mainly with weight-bearing activities. Several nonoperative therapies remain as the first choices, but there is still no consensus on which is the most effective. This study aimed to systematically synthesize the evidence regarding the effectiveness of PRP in the management of ankle OA. Searches were conducted on PubMed, Cochrane, CINAHL, and SPORTDiscus to find relevant articles from inception to December 2023. Details regarding study characteristics, PRP procedures, and outcomes were extracted. A quality assessment was developed according to Joanna Briggs Institute’s critical appraisal tool. A total of five studies met the inclusion criteria, with 184 patients receiving PRP therapy (mean age 55.7 years, and 51.1% were female). There were three case series, one prospective cohort, and one randomized controlled trial. Pain and function were the most frequently evaluated outcomes among the selected articles. They showed significant improvements in the short-term follow-ups, mostly in patients with II-III-stage ankle OA. There is currently insufficient evidence regarding the effectiveness and safety of PRPs in the treatment of ankle OA. A paucity of high-level research in the literature was also found.
Keywords: Artrosis - Investigación; Tobillos - Fisioterapia; Ankle joint; Osteoarthritis; Growth factors; Cartilage